2012
DOI: 10.3109/00365548.2012.681696
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance and characteristics of pleural effusion in patients with Mycoplasma pneumoniae pneumonia

Abstract: Data regarding parapneumonic pleural effusion in Mycoplasma pneumoniae pneumonia (MP) patients are limited. In this study MP patients with pleural effusion tended to be younger and had longer hospital stays and more common use of systemic steroids compared to those without pleural effusion. In 5 of the 6 patients for whom pleural fluid data were available, the pleural effusion was lymphocyte-predominant rather than polymorphonuclear leukocyte-predominant; these patients also had elevated adenosine deaminase le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 19 publications
1
18
2
Order By: Relevance
“…Higher IL17A expression in BALF is correlated with general MPP and MPP without pleural effusion; lower IL17A expression in BALF is correlated with refractory MPP and MPP with pleural effusion. Similar to our results, it has been reported that MPP children with pleural effusion may have a more severe form of MPP with longer hospital stay and more commonly usage of corticosteroid comparing to those without pleural effusion 5 . We put forward the hypothesis that low IL17A levels in BALF may suggest severe MPP in children and more likely to become MPP with pleural effusion and refractory MPP.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Higher IL17A expression in BALF is correlated with general MPP and MPP without pleural effusion; lower IL17A expression in BALF is correlated with refractory MPP and MPP with pleural effusion. Similar to our results, it has been reported that MPP children with pleural effusion may have a more severe form of MPP with longer hospital stay and more commonly usage of corticosteroid comparing to those without pleural effusion 5 . We put forward the hypothesis that low IL17A levels in BALF may suggest severe MPP in children and more likely to become MPP with pleural effusion and refractory MPP.…”
Section: Discussionsupporting
confidence: 92%
“…Severe MPP may have pleural effusion, longer fever duration and refractoriness. It has been reported that MP patients with pleural effusion may have a more severe form MPP compared to those without pleural effusion 5 . The mechanism of refractory MPP is not clear, one possible cause is the inflammatory response caused by immune abnormalities.…”
Section: Introductionmentioning
confidence: 96%
“…On the contrary, they observed elevated ADA levels in five patients, but our patient's ADA level was low, acid fast bacilli stains were negative and the neutrophilic exudate culture was negative for bacterial or viral organisms [21] . Retrospective analysis done by Linz DH et al; showed five patients had pleural effusion which were moderate to large size, two patients had diagnostic thoracentesis which showed exudate with neutrophilic predominant effusion [22] .…”
Section: Discussioncontrasting
confidence: 77%
“…We checked for consolidation, ground glass opacity (GGO), centrilobular nodules, bronchial wall thickening, cavity, and pleural effusion. Similar to previous studies 20 21 , patients were classified into four levels by measuring the maximum fluid thickness between the visceral and parietal pleurae on a CT scan: no pleural effusion; small pleural effusion, fluid thickness of 5-20 mm; moderate pleural effusion, fluid thickness of 21-50 mm; and large pleural effusion, fluid thickness >50 mm.…”
Section: Methodsmentioning
confidence: 99%